PENGARUH BUDAYA ISLAM, KEMAMPUAN MANAJEMEN TERHADAP KINERJA KARYAWAN BANK SYARIAH INDONESIA MELALUI MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Oktaviansyah, Hendrik Tri; Alfi Arif; Robby Reza Zulfikar (Study Program of Management Faculty of Economics and Business University of Jember, 2025)
This research aims to determine the influence of Islamic culture and management capability on the performance of employees at Bank Syariah Indonesia through work motivation as a mediating variable. This study was conducted at Bank Syariah Indonesia, which is considered the largest bank in Indonesia. The results of the study indicate that Islamic culture has a positive influence on work motivation, management capability has a positive influence on work motivation, work motivation has a significant positive influence on employee performance, Islamic culture has a positive and significant influence on employee performance, management capability has a positive and significant influence on employee performance, and the influence of Islamic culture on employee performance through work motivation is significant, as well as the influence of management capability on employee performance through work motivation being significant